The Urgency of Sharia-Based Financial Management for Investment in the Halal Product Industry - Zakaria Suronoto; Jamlia Limehuway; J. Jasmin (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to analyze the urgency of Sharia-based financial management in promoting investment in the halal product industry and to identify the challenges and strategic implications for strengthening the halal ecosystem in Indonesia. The study employed a qualitative approach using the Systematic Literature Review (SLR) method based on the PRISMA 2020 guidelines. Data were collected from scholarly articles indexed in Google Scholar, Scopus, Dimensions, Garuda, and Crossref, published between 2020 and 2025. The findings indicate that Sharia-based financial management plays a significant role in enhancing investor confidence, expanding access to financing, reducing investment risks, and supporting the sustainability of the halal industry. Nevertheless, its implementation faces several challenges, including low levels of Islamic financial literacy, limited access to financing, inadequate integration of the halal ecosystem, and a lack of Sharia-compliant investment instruments that support the halal industry. This study confirms that Sharia-based financial management serves as a strategic foundation for sustainable investment development in the halal industry. The findings contribute theoretically to the advancement of Islamic economics and provide practical implications for policymakers, Islamic financial institutions, and halal industry stakeholders in strengthening the competitiveness of the national halal economy